A methods engineering study on Garjel Bag Industry - Aspera, Romeo (College of Engineering, 2002)
This study aims to apply methods engineering techniques to an existing manufacturing company. The proponents of the study chose Garjel Bag Industry based in Sampaloc, Manila as project site, which particularly manufactures wallets. Through interviews and actual observations done during plant visits, problems existing in the company were identified and analyze. The proponents chose three problem areas, which are high workload to worker ratio, defective cutter tools and insufficient maintenance, where methods engineering can be applied and within the control of Garjel. Alternative solutions to the problems were generated. Using the data gathered such company resources, existing processes and SWOT Analysis done by the proponents, evaluation of alternatives including the status quo by decision analysis was done to be able to select the best solution. In addressing high workload to worker ratio, grouping the production area into workstations should be done. While for defective cutter tools and insufficient maintenance, buying new specialized tools and making the workers responsible for the maintenance respectively, are the proposed to be the best solutions. Implementation plans for each preferred solution were prepared. With the organizational structure of the company, people responsible for the implementation plan's activities were identified. The overall-in-charge for the implementation of such solutions for all problems was assigned to the manager. Gantt chart was also presented for each solution to indicate the time that may consume for implementing each proposed solution. Implementing line balancing will take 18 working hours. For buying new cutter tools, this will consume 7 3/4 days since canvassing will be done. And for the maintenance scheme, two plans were proposed. The first plan, which addressed the maintenance of the machines, will take 9.5 hours while the second plan, which addressed maintenance of the cutter tools, will take 17 hours. This study proved the usefulness of methods engineering techniques in addressing problems existing in manufacturing companies. However, the techniques provided were just few of the many. Thus, further study to validate the result of the study should be done particularly in problem identification and analysis, methods study and work measurement.